MicroRNA-218 inhibits the proliferation and metastasis of esophageal squamous cell carcinoma cells by targeting BMI1 - WANG, TING (Int J Mol Med, 2015)
MicroRNAs (miRNAs or miRs) play a pivotal role in esophageal carcinogenesis either as oncogenes or as tumor suppressor genes. In the present study, we found that the expression level of miR-218 was significantly reduced in esophageal squamous cell carcinoma (ESCC) tissues and ESCC cell lines. Moreover, its expression was found to correlate with the clinicopathological stage of ESCC; miR-218 expression was lower in the stage III tissue samples than in the stage I and II tissue samples. Furthermore, the decreased expression of miR-218 was found to be associated with an enhanced ESCC cell proliferation and metastasis. Western blot analysis and luciferase reporter assay revealed that miR-218 decreased BMI1 expression by binding to the putative binding sites in its 3′-untranslated region (3′-UTR). The BMI1 mRNA expression levels were markedly increased and negatively correlated with the miR-218 expression level in the ESCC tissues. Functional analyses revealed that the restoration of miR-218 expression inhibited ESCC cell proliferation, migration and invasion and promoted apoptosis. The knockdown of BMI1 by siRNA showed the same phenocopy as the effect of miR-218 on ESCC cells, indicating that BMI1 was a major target of miR-218. In the present study, our findings confirm miR-218 as a tumor suppressor and identify BMI1 as a novel target of miR-218 in ESCC. Therefore, miR-218 may prove to be a useful biomarker for monitoring the initiation and development of ESCC, and may thus be an effective therapeutic target in ESCC.